Diet Therapy in the Management of Inflammatory Bowel Diseases (IBD) and Irritable Bowel Syndrome (IBS): Evaluation of the Low-FODMAP Diet for Treatment (Research, Society and Development, 2025)
Inflammatory Bowel Diseases (IBD), including Crohn’s disease, ulcerative colitis, and syndromes such as Irritable Bowel Syndrome (IBS), are chronic conditions characterized by recurrent inflammation of the gastrointestinal tract (GI). This study aims to analyze the use of a low-FODMAP diet as diet therapy in the management of inflammatory bowel diseases, evaluating its impact on symptom reduction, patients’ quality of life, and modulation of the inflammatory response. This is a literature review analyzing published studies that focus on evidence regarding the application of the diet in the treatment of IBD and gastrointestinal syndromes. According to the literature, treatment with a low-FODMAP diet has a significant impact on the manifestation and severity of symptoms in most patients. In this context, diet therapy—which involves strategies aimed at adjusting food intake to reduce intestinal inflammation and relieve symptoms—has become an increasingly valued approach. It is concluded that the low-FODMAP diet is an effective dietary strategy in the management of Inflammatory Bowel Diseases (IBD) and Irritable Bowel Syndrome (IBS), promoting significant improvement in gastrointestinal symptoms as well as in patients’ quality of life. Scientific literature points to notable benefits in modulating the inflammatory response and reducing associated discomforts such as abdominal pain, bloating, flatulence, and diarrhea. Although more controlled clinical studies are still needed to standardize the application of this nutritional approach, the available data support its use as a valuable complementary tool in the treatment of these chronic conditions.